Repositioning of Ahmed glaucoma valve tube in the anterior chamber with prolene sutures to manage tube-endothelial touch - Dada, T; Gupta, R; Tinwala, S I; Sobti, A; Panda, A (Nepalese Journal of Ophthalmology, 2012)
Background: Corneal endothelial damage is a known complication of aqueous shunt surgery. Objective: To describe a new technique for repositioning the Ahmed glaucoma valve tube in a case of tube-endothelial touch. Case: A patient with advanced glaucoma, having undergone Ahmed glaucoma valve (AVG) implantation, developed localized corneal endothelial damage due to contact between the tube and superior corneal endothelium. Two 10-0 prolene anchor sutures were passed over the tube in the anterior chamber, repositioning it away from the endothelium, thus preventing further damage to the corneal endothelium. Resolution of corneal oedema was noted without affecting the tube drainage and intraocular pressure. Conclusion: Intracameral repositioning of the shunt tube using prolene sutures is a useful technique for correcting the tube malposition. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6549 Nepal J Ophthalmol 2012; 4 (2): 309-411